2007
DOI: 10.1136/ard.2007.073452
|View full text |Cite
|
Sign up to set email alerts
|

One-year follow-up of Coll2-1, Coll2-1NO2and myeloperoxydase serum levels in osteoarthritis patients after hip or knee replacement

Abstract: The normalisation of Coll2-1 levels 3 months after surgery indicates that Coll2-1 is a disease-specific marker that is sensitive to the structural changes occurring in a single joint. Furthermore, the immunohistochemical findings are consistent with the concept that the major source of serum Coll2-1 is the damaged articular cartilage. Finally, serum MPO levels decreased after joint replacement indicating that neutrophil activation occurs in OA joints, even in the late stage of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 44 publications
4
50
2
Order By: Relevance
“…This study positioned Coll2-1 and Coll2-1 NO 2 biomarkers in the framework of biomarkers applied to the development of drugs intended for the treatment of OA as described in the recent published work by Kraus et al 35 Previous works reporting Coll2-1 and Coll2-1 NO 2 levels have fulfilled the step of exploration based on pre-clinical evidence [18][19][20][21][22] and the further step of demonstration giving evidence that support the primary clinical evidence in both healthy and OA patients. 16,17,23 The Coll2-1 AND Coll2-1 NO 2 LEVELS AFTER VISCOSUPPLEMENTATION 905 present study gave the first evidence to the next step of characterization. These steps have also equivalence in the nomenclature suggested in the guidance by the Federal Drug Administration.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This study positioned Coll2-1 and Coll2-1 NO 2 biomarkers in the framework of biomarkers applied to the development of drugs intended for the treatment of OA as described in the recent published work by Kraus et al 35 Previous works reporting Coll2-1 and Coll2-1 NO 2 levels have fulfilled the step of exploration based on pre-clinical evidence [18][19][20][21][22] and the further step of demonstration giving evidence that support the primary clinical evidence in both healthy and OA patients. 16,17,23 The Coll2-1 AND Coll2-1 NO 2 LEVELS AFTER VISCOSUPPLEMENTATION 905 present study gave the first evidence to the next step of characterization. These steps have also equivalence in the nomenclature suggested in the guidance by the Federal Drug Administration.…”
Section: Discussionsupporting
confidence: 52%
“…16,17 These biomarkers have been validated in vivo in mouse, guinea pig and horse [18][19][20][21][22] and also in healthy human 16 and OA patients. 17,23 The aim of this study was to measure the evolution of the serum levels of Coll2-1 and Coll2-1 NO 2 in knee OA patients after VS. This study is part of the Biovisco study and this article is the continuation of the previous one which has reported the concentrations of the following biomarkers: CTXII, COMP, C 2 C, CS846, HA, PIICP.…”
mentioning
confidence: 99%
“…Another new biomarker of cartilage damage is Fibulin-3, which in turn is derived from extracellular matrix proteins [20,21]. These biomarkers are correlated with the severity of OA, but in our study, urinary levels of Coll2-1, Coll2-1NO2 and Fibulin-3 were not reduced in any of the studied groups.…”
Section: Discussioncontrasting
confidence: 41%
“…These results are in agreement with previous studies by Yazici et al [10] and Baskol et al [12] , who observed a relationship between MPO and biomarkers of inflammatory activity (CRP, ESR and WBC). Steinbeck et al [4] reported that patients with early osteoarthritis displayed high levels of MPO, whereas Deber et al [32] found that serum MPO levels decreased after joint replacement, indicating that neutrophil activation occurs in osteoarthritic joints, even in late stages of the disease.…”
Section: Discussionmentioning
confidence: 99%